Demonstration of a laser powder bed fusion combinatorial sample for high-throughput microstructure and indentation characterization. (1st November 2021) - Weaver, Jordan S.; Pintar, Adam L.; Beauchamp, Carlos; Joress, Howie; Moon, Kil-Won; Phan, Thien Q.
Graphical abstract: Highlights: Ninety-six regular samples, sixty unique processes into four combinatorial samples. Estimated five times reduction in time and cost. Hardness was most influenced by stress-relieving and sample geometry. Abstract: High-throughput experiments that use combinatorial samples with rapid measurements can be used to provide process-structure-property information at reduced time, cost, and effort. Developing these tools and methods is essential in additive manufacturing where new process-structure-property information is required on a frequent basis as advances are made in feedstock materials, additive machines, and post-processing. Here we demonstrate the design and use of combinatorial samples produced on a commercial laser powder bed fusion system to study 60 distinct process conditions of nickel superalloy 625: five laser powers and four laser scan speeds in three different conditions. Combinatorial samples were characterized using optical and electron microscopy, x-ray diffraction, and indentation to estimate the porosity, grain size, crystallographic texture, secondary phase precipitation, and hardness. Indentation and porosity results were compared against a regular sample. The smaller-sized regions (3 mm × 4 mm) in the combinatorial sample have a lower hardness compared to a larger regular sample (20 mm × 20 mm) with similar porosity (<0.03%). Despite this difference, meaningful trends were identified with the combinatorial sample for grain size, crystallographic texture, and porosity versus laser power and scan speed as well as trends with hardness versus stress-relief condition.